The database of hydroecological monitoring of the Narochanskie lakes (Belarus) - Adamovich, Boris V.; Mikheeva, Tamara M.; Kovalevskaya, Raisya Z.; Zhukova, Tatiana V.; Dubko, Natalia V.; Nikitina, Ludmila V.; Makarevich, Tamara A.; Makarevich, Tamara A.; Savich, Iryna V.; Veres, Yulia K.; Selivonchik, Iryna N.; Kruk, Daria V. (Experimental Biology and Biotechnology, 2024)
The hydroecological monitoring of the Narochanskie lakes hold a special place in the system of monitoring of water bodies. Since 1978, researchers from the laboratory of hydroecology and the Naroch Biological Station named after G. G. Vinberg of the faculty of biology of the Belarusian State University have been conducting year-round monitoring of the Naroch, Myastro and Batorino lakes located in northwestern Belarus. This paper presents a description of an hydroecological database compiled from scattered electronic and printed materials from the laboratory of hydroecology and the Naroch Biological Station named after G. G. Vinberg as part of a series of scientific projects. The database consists of eight tables: «Hydrochemistry», «Temperature and oxygen», «Phytoplankton (integrated samples)», «Phytoplankton (samples by layers)», «Zooplankton», «Zoobenthos», «Bacterioplankton», «Primary production». Each row in the database has the necessary attributes, allowing data from all tables to be combined for each specific sample collection. The database allows for a quick and in-depth analysis of the relationships between the main hydroecological parameters of the lakes. Long-term observation series with a large number of parameters make it possible to analyse long-term trends in changes of lake’s ecosystems caused by climatic and anthropogenic factors.